UNRAVELING THE RIGHT TO LIFE IN CASES OF DEATHS RESULTING FROM THE ACTIONS OF STATE AGENTS UNDER THE SYSTEM OF ECHR - Listiningrum, Prischa (Faculty of Law, Universitas Brawijaya, 2017)
it shall be done in a certain threshold of necessity. In particular when the taken of life is done by the agents of states. This article examines the interpretation of article 2 by the European Court of Human Rights, especially when it is read in conjunction with state's positive obligations under article 1. The discussion will proceed in three sections: first, the review of the evolvement of the procedural requirements of article 2 in cases of deaths arising from the acts of state agents. Second, is the examination of whether the procedural requirements of article 2 can be used as a mean in securing the adequate protection of the right to life from arbitrary killing by the use of lethal force. Third, is an analysis of an effective legal system as a procedural requirement of article 2 in the case of homicide caused by the negligence of the authorities. Finally, this essay will conclude by examining the Court's position in its endeavours to achieve an appropriate balance between not over-burdening its Member States and securing the adequate protection of the right to life.